About Sectoral Statistical Toolkit and Statistical Data on the Number of Foreign Students - O. N. Gutsynuk; A. V. Ridiger (Informaciâ i Innovacii, 2023)
The development of the export of education and international scientific and educational communication is an important task assigned to the federal executive bodies of the Russian Federation. However, there are reasons that impede the development of international scientific and educational cooperation. The article, based on the results of analysis of statistics in the field of export of educational services, considers the development of sectoral statistical tools for monitoring international educational cooperation.